Захист інформації у системах голосової автентифікації - Квашенко, В. Р. (ХНУРЕ, 2023)
Voice authentication has gained significant attention as a biometric security measure in various applications, including mobile devices, financial services, and access control. However, it introduces unique cybersecurity challenges. This paper explores the evolving landscape of voice authentication, delving into vulnerabilities and countermeasures to ensure the integrity and privacy of user data. From voice imitation attacks to the intricacies of secure voice biometrics, we discuss the multifaceted dimensions of voice-based security. This research aims to contribute to the growing field of cybersecurity in voice authentication systems.
Keywords: захист інформації; голосова автентифікація